Prediction of Hemorrhagic Transformation After Ischemic Stroke: Development and Validation Study of a Novel Multi-biomarker Model - Liu, Junfeng; Wang, Yanan; Jin, Yuxi; Guo, Wen; Song, Quhong; Wei, Chenchen; Li, Jing; Zhang, Shanshan; Liu, Ming (Frontiers in Aging Neuroscience, 2021)
Objectives:We aimed to develop and validate a novel multi-biomarker model for predicting hemorrhagic transformation (HT) risk after acute ischemic stroke (AIS).Methods: We prospectively included patients with AIS admitted within 24 hours of stroke from January 1st 2016 to January 31th 2019. A panel of 17 circulating biomarkers was measured and analyzed in this cohort. We assessed the ability of individual circulating biomarkers and the combination of multiple biomarkers to predict HT, symptomatic HT (sHT) and parenchymal hematoma (PH) after AIS. The strategy of multiple biomarkers in combination was then externally validated in an independent cohort of 288 Chinese patients. Results: A total of 1207 patients with AIS (727 males; mean age, 67.2±13.9 years) were included as a derivation cohort, of whom 179 patients (14.8%) developed HT. The final multi-biomarker model included 3 biomarkers (platelets, neutrophil-to-lymphocyte ratios [NLR], and high-density lipoprotein[HDL]) from different pathways, showing a good performance for predicting HT in both the derivation cohort (c statistic=0·64, 95% CI 0·60–0·69), and validation cohort (c statistic=0·70, 95% CI 0·58–0·82).Adding these 3 biomarkers simultaneously to the basic model with conventional risk factors improved the ability of HT reclassification(net reclassification improvement 65.6%, P< 0.001), PH (net reclassification improvement 64.7%, P< 0.001), and sHT (net reclassification improvement 71.3%, P< 0.001). Conclusion: This easily applied multi-biomarker model had a good performance for predicting HT in both the derivation and external validation cohorts. Incorporation of biomarkers into clinical decision making may help to identify patients at high risk of HT after AIS and warrants further consideration.